Mechanical properties of high density packed silica/poly(vinyl chloride) composites. Issue 7 (28th November 2012) - Conradi, M.; Zorko, M.; Jerman, I.; Orel, B.; Verpoest, I.
Abstract This article focuses on the preparation and mechanical properties of silica/poly(vinyl chloride) (PVC) composites enriched with 60% mass ratio of 130 nm and 30 nm silica sphere fillers. Silica particles were pre‐treated with silane, IO7 T7(OH)3 (trisilanol isooctyl polyhedral‐oligomeric silsesquioxane) to prevent agglomeration. The dispersion and interfacial compatibility of silica particles in a PVC matrix were investigated by scanning electron microscopy. The composite mechanical properties were characterized by tensile test, revealing improved Young modulus and tensile strength. Compared to pure PVC, the stiffness of 30 nm and 130 nm silica/PVC composites is on average increased by 30–40%, respectively. Similar trend was observed for the composite tensile strength on the change of the silica size. In contrast, elongation at break decreased for both composites compared to pure PVC, for 15% in 30 nm and for 30% in 130 nm silica/PVC composite. POLYM. ENG. SCI., 2013. © 2012 Society of Plastics Engineers